Characterizing stomatal attributes and photosynthetic induction in relation to biochemical changes in Coriandrum sativum L. by foliar-applied zinc oxide nanoparticles under drought conditions - Ahmed, Shakil; Khan, Muhammad Tajammal; Abbasi, Asim; Haq, Inzamam Ul; Hina, Aiman; Mohiuddin, Muhammad; Tariq, Muhammad Atiq Ur Rehman; Afzal, Muhammad Zaheer; Zaman, Qamar uz; Ng, Anne Wai Man; Li, Yong (Frontiers in Plant Science, 2023)
Abiotic stress, particularly drought, will remain an alarming challenge for sustainable agriculture. New approaches have been opted, such as nanoparticles (NPs), to reduce the negative impact of drought stress and lessen the use of synthetic fertilizers and pesticides that are an inevitable problem these days. The application of zinc oxide nanoparticles (ZnO NPs) has been recognized as an effective strategy to enhance plant growth and crop production during abiotic stress. The aim of the current study was to investigate the role of ZnO NPs in drought stress management of drought-susceptible Coriandrum sativum L. (C. sativum) in two consecutive seasons. Drought regimes (moderate drought regime—MDR and intensive drought regime—IDR) were developed based on replenishment method with respect to 50% field capacity of fully irrigated (control) plants. The results showed that foliar application of 100 ppm ZnO NPs improved the net photosynthesis (Pn), stomatal conductance (C), and transpiration rate (E) and boosted up the photosynthetic capacity associated with photosynthetic active radiation in MDR. Similarly, 48% to 30% improvement of chlorophyll b content was observed in MDR and onefold to 41% in IDR during both seasons in ZnO NP-supplemented plants. The amount of abscisic acid in leaves showed a decreasing trend in MDR and IDR in the first season (40% and 30%) and the second season (49% and 33%) compared with untreated ZnO NP plants. The ZnO NP-treated plants showed an increment in total soluble sugars, total phenolic content, and total flavonoid content in both drought regimes, whereas the abaxial surface showed high stomatal density and stomatal index than the adaxial surface in foliar-supplied NP plants. Furthermore, ZnO NPs improve the magnitude of stomata ultrastructures like stomatal length, stomatal width, and pore length for better adaptation against drought. Principal component analysis revealed the efficacy of ZnO NPs in inducing drought tolerance in moderate and intensive stress regimes. These results suggest that 100 ppm ZnO NPs can be used to ameliorate drought tolerance in C. sativum plants.